Characterization of Terminators in Saccharomyces cerevisiae and an Exploration of Factors Affecting Their Strength. (15th November 2017) - Wei, Linna; Wang, Zhaoxia; Zhang, Genlin; Ye, Bangce
Abstract: Terminators in eukaryotes play an important role in regulating the transcription process by influencing mRNA stability, translational efficiency, and localization. Herein, the strengths of 100 natural terminators in Saccharomyces cerevisiae have been characterized by inserting each terminator downstream of the TYS1p‐enhanced green fluorescent protein (eGFP) reporter gene and measuring the fluorescent intensity (FI) of eGFP. Within this library, there are 45 strong terminators, 31 moderate terminators, and 24 weak terminators. The strength of these terminators, relative to that of PGK1t standard terminator, ranges from 0.0613 to 1.8002, with a mean relative FI of 0.9945. Mutating the control elements of terminators further suggests that the efficiency element has an important effect on terminator strength. The use of strong terminators will result in an enhanced level of mRNA and protein production; this indicates that gene expression can be directly influenced by terminator selection. Pairing a terminator with an inducible promoter or a strong constitutive promoter has less effect on gene expression; however, pairing with a week promoter will significantly increase the level of gene expression. Through exchange of the reporter genes, it can be demonstrated that the terminator functions as a genetic component and is independent of the coding region. This work demonstrates that the terminator is an important regulatory element and can be considered in applications for the fine‐tuning of gene expression and metabolic pathways. Abstract : Controlling functions : A library of 100 terminators in Saccharomyces cerevisiae are selected to investigate their mechanism and function. The terminator functions as a genetic component and is independent of the coding region. As an important regulatory element, the terminator is available for the fine‐tuning of gene expression and metabolic pathways.